Investigation of Adsorptive Properties of Surfactant Modified Sepiolite for Removal of Ciprofloxacin: Pharmaceutical Science-Pharmaceutical analysis for Novel drug formulation - Davoud Balarak; Mohadeseh Zafariyan; Shaziya Siddiqui (International Journal of Life Science and Pharma Research, 2022)
Pharmaceutical residues, which are considered as emerging contaminants, have been frequently detected in various water including treated water, surface water, and underground water. Furthermore, it may pose a serious risk to the living organisms by enhancing bacterial drug resistance. However, the removal of CIP from aqueous solution is difficult by present water treatment methods. The previous study indicated that the removal of CIP by conventional wastewater treatment technologies is generally incomplete. The aim of this study was to evaluate the efficiency of surfactant (cetyltri-methyl- ammonium bromide)-modified Sepiolite (SMS) for Ciprofloxacin antibiotics (CIP) adsorption in a batch mode technique. The effects of different system variables, adsorbent dosage, initial CIP concentration, temperature contact time were investigated and optimal experimental conditions were ascertained. The results showed that as the amount of the adsorbent is increased, the percentage of CIP removal increase accordingly. Optimum temperature value for CIP adsorption was 50 . Maximum CIP was sequestered within 60 min from the start of every experiment. The results also showed that the best test conditions were obtained at i) initial concentration of CIP 10 mg/L and adsorbent dosage 2 g/L as working solution have been selected as the optimum conditions by the batch process; ii) the removal percentage and the maximum adsorption capacity were found to be 99.1% and 63.84 mg/g iii) Four well-known kinetic models, the pseudo-first- and pseudo-second-order, Elovich and Intra-particle diffusion were used to correlate the adsorption kinetic data, with the pseudo-second-order model giving better results; iv) Negative value of ∆Go and positive value of ∆Hº indicates the feasibility of the process and indicates the spontaneous and endothermic nature of the adsorption; v) SMS adsorbent can be an attractive option for CIP antibiotic removal from diluted industrial effluents since test reaction made on simulated antibiotic wastewater showed better removal percentage of CIP.